Efeito de um extrato de chrysobalanus icaco na marcação de constituíntes sanguíneos com tecnécio-99m, na morfologia de hemácias, na topologia plasmidial e na ação do cloreto estanoso no dna plasmidial - Presta, Giuseppe Antônio (2007)
﻿The use of radionuclides has contributed for advances in Health Sciences, to research or to the diagnosis and/or treatment of diseases. These advances have been possible with the utilization of radiopharmaceuticals labeled with technetium-99m (99mTc). Stannous chloride (SnCl2) has the main reducing agent utilized to obtain radiopharmaceuticals labeled with technetium-99m. It has been reported that several natural or synthetic drugs are capable to alter the labeling of blood constituents with 99mTc, as well as the red blood cells morphology. The aim of this study was to evaluate possible alterations of Chrysobalanus icaco extract on the labeling of blood constituents with 99mTc, on the morphology of RBC of blood of Wistar rats, on the breakage of plasmid DNA and on the effects of stannous chloride on plasmid DNA. The results showed significant (P<0.05) alteration of the labeling of blood constituents with 99mTc, as well as, modification of the morphology and morphometry (perimeter/area ratio) of the RBC in presence of the extract. These data suggest that this abajeru extract could alter the labeling of blood constituents with 99mTc by its chelating/antioxidant action and/or effects on membrane structures. Moreover C. icaco extract altered the electrophoretic profile and decreased significantly (p<0.05) the effect of SnCl2 on plasmid DNA. The results obtained in this work could indicate a dose-dependent protective action against the SnCl2 and a genotoxic effect of C. icaco extract on plasmid DNA